MATERIAL EXPLORATION OF GLULAM IN SHELTER DESIGN USING CHANNEL OF CREATIVITY: FOCUS ON MATERIAL - Nareswarananindya, Nareswarananindya (Border: Jurnal Arsitektur, 2019)
Characteristics of material can be explored and used as a channel of creativity in designing buildings. Nevertheless, the material exploration process must be able to support efficient use of resources throughout the building's life cycle, starting from material selection, design, construction, maintenance, to demolition. Glued Laminated Timber (Glulam) is an alternative material which is wood-based materials, can be renewed and has low embodied energy. By using channel of creativity (focus on material, the characteristics of glulam are used as an approach to designing a building. The type of building that used as an object of exploration is a simple non-space building, called shelter. The design process is a cyclical series of phases: analysis, synthesis, and evaluation to obtain the most appropriate design. The analysis phase (glulam, shelter, and focus on material) create design criteria that will be used to produce several alternative designs at the synthesis stage. Then, some alternative designs are evaluated at the evaluation stage to get the most appropriate design. This research aims to find out schematic design of shelter in the form of single curves and double curves, composed of 60x60 cm glulam elements joined with notched technique.